PRIMEIRO RELATO DE Puccinia mogiphanis EM Alternanthera brasiliana NO MATO GROSSO DO SUL - Gomes Cavalcanti , Vittor; Fernandes da Costa , Brenda; André Sganzerla Graichen , Felipe; Henrique Martinez Blanco , Neder; de Souza da Silva , Talísia; Idelfonso Oliveira , Thalita (ANAIS DO ENIC, 2026)
-